2018
DOI: 10.1177/1756284818811294
|View full text |Cite
|
Sign up to set email alerts
|

Advances in therapeutic options for portal hypertension

Abstract: Portal hypertension represents one of the major clinical consequences of chronic liver disease, having a deep impact on patients’ prognosis and survival. Its pathophysiology defines a pathological increase in the intrahepatic vascular resistance as the primary factor in its development, being subsequently aggravated by a paradoxical increase in portal blood inflow. Although extensive preclinical and clinical research in the field has been developed in recent decades, no effective treatment targeting its primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 163 publications
(191 reference statements)
1
24
0
1
Order By: Relevance
“…Also, the difference in MELD score, MELD-Na score, portal vein CI and Hepatic A. RI between patients with complication (SBP, HRS and bleeding OV) and those without was statistically insignificant in both groups. This could provide new insights on unusual targetable molecular pathways and metabolites that may affect the outcome in such patients [20]. In addition, our study revealed high statistically significant difference in MELD score, MELD-Na score between patients complicated with hepatic encephalopathy and those without in both groups and high statistically significant difference in PV congestive index and hepatic A RI in hyponatremic group only.…”
Section: Discussionsupporting
confidence: 50%
“…Also, the difference in MELD score, MELD-Na score, portal vein CI and Hepatic A. RI between patients with complication (SBP, HRS and bleeding OV) and those without was statistically insignificant in both groups. This could provide new insights on unusual targetable molecular pathways and metabolites that may affect the outcome in such patients [20]. In addition, our study revealed high statistically significant difference in MELD score, MELD-Na score between patients complicated with hepatic encephalopathy and those without in both groups and high statistically significant difference in PV congestive index and hepatic A RI in hyponatremic group only.…”
Section: Discussionsupporting
confidence: 50%
“…Because resources are limited, only a minority of the emerging treatment approaches are tested in phase 3 clinical trials assessing direct endpoints, which greatly inhibits scientific progress in the field of PH. (21) Thus, we aimed to assess the impact of pretreatment HVPG, changes in HVPG, and posttreatment values on the development of hepatic decompensation in patients with PH who achieved SVR to IFN-free therapy. Moreover, we investigated the use of transient elastography (TE) and von Willebrand factor (VWF) for monitoring the evolution of PH and the impact of HCV cure on markers of bacterial translocation and inflammation.…”
Section: Changes In Hepatic Venous Pressure Gradient Predict Hepatic mentioning
confidence: 99%
“…This is particularly problematic in patients with cACLD, in whom the incidence of hepatic decompensation is comparatively low, resulting in tremendously larger trials and longer study periods, if clinical endpoints (e.g., hepatic decompensation) are assessed. Because resources are limited, only a minority of the emerging treatment approaches are tested in phase 3 clinical trials assessing direct endpoints, which greatly inhibits scientific progress in the field of PH …”
mentioning
confidence: 99%
“…Improvement of ACLD might be accomplished with the cessation of injury or by drug‐induced amelioration of hepatic cells . Unfortunately, current options to improve ACLD and its main clinical complications are limited, and although statins have shown beneficial effects on portal hypertension and survival, the risk reduction afforded by these and other agents is limited, indicating that new therapeutic strategies are warranted.…”
mentioning
confidence: 99%